A study on atomic number and energy dependence of coherent scattering coefficients - Gurler, Orhan; Kaynak, G.; Yalcin, S.; Oktar, C. H. (Elsevier BV, 2013)
Abstract This study presents an analytic formula for calculation of the coherent attenuation coefficients of gamma rays for 100 elements in the energy range from 0.01 to 3 MeV. The analytic formula is based on WinXCOM. Comparisons were made of the analytic coherent attenuation coefficients with the coherent attenuation coefficients calculated with the WinXCOM. The results obtained with the analytic approach agree well with those calculated with the WinXCOM.
Keywords: 7. Clean energy